Measuring Cyberbullying Levels among Adolescents in Integrated Islamic Junior High Schools in Jambi City: An Implementation of the Rasch Model - Riska Amalya Nasution; Meinarisa Meinarisa; Ilham Falani (Universitas Ahmad Dahlan, 2024)
The incidence of cyberbullying in adolescents is increasing. This is, in part, attributed to the progress of Science and Technology (IPTEK), which is inseparable from the negative impact of cyberbullying. The latter has become central to adolescent communication. Consequently, cyberbullying, especially among adolescents, demands serious attention for early intervention. The purpose of this study was to measure the level of cyberbullying among students at SMP IT Jambi City by implementing the Rasch Model, a modern theoretical approach enhancing the accuracy of measuring latent variables. The research included 91 students from classes VII and VIII, selected through proportional random sampling. Data collection employed the Cyber Victim and Bullying Scale (CVBS) with 28 questions. The Rasch Model analysis revealed a high level of cyberbullying among adolescents at SMP IT Jambi City, with 52.2% categorized as high and 47.8% as low. The results demonstrated high accuracy, evident in validity and reliability coefficients of 0.87 and 0.71, respectively. This research provides valuable information for stakeholders aiming to maintain a cyberbullying-free climate.